Book Review - Verma, Rabindra Kumar (East European Journal of Psycholinguistics, 2020)
Susheel Kumar Sharma’s Unwinding Self: A Collection of Poems. Cuttack: Vishvanatha Kaviraj Institute, 2020, ISBN: 978-81-943450-3-9, Paperback, pp. viii + 152.Like his earlier collection, The Door is Half Open, Susheel Kumar Sharma’s Unwinding Self: A Collection of Poems has three sections consisting of forty-two poems of varied length and style, a detailed Glossary mainly on the proper nouns from Indian culture and tradition and seven Afterwords from the pens of the trained readers from different countries of four continents. The structure of the book is circular. The first poem “Snapshots” indicates fifteen kaleidoscopic patterns of different moods of life in about fifteen words each. It seems to be a rumination on the variegated images of everyday experiences ranging from individual concerns to spiritual values. Art-wise, they can be called mini-micro-poems as is the last poem of the book.  While the character limit in a micro poem is generally 140 (the character limit on Twitter) Susheel has used just around 65 in each of these poems. Naturally, imagery, symbolism and cinematic technique play a great role in this case. In “The End of the Road” the poet depicts his individual experiences particularly changing scenario of the world. He seems to be worried about his eyesight getting weak with the passage of time, simultaneously he contrasts the weakness of his eyesight with the hypocrisy permeating the human life. He compares his diminishing eyesight to Milton and shows his fear as if he will get blind. He changes his spectacles six times to clear his vision and see the plurality of a reality in human life. It is an irony on the changing aspects of human life causing miseries to the humanity. At the end of the poem, the poet admits the huge changes based on the sham principles: “The world has lost its original colour” (4). The concluding lines of the poem make a mockery of the people who are not able to recognise reality in the right perspective.         The poem “Durga Puja in 2013” deals with the celebration of the festival “Durga Puja” popular in the Hindu religion. The poet’s urge to be with Ma Durga shows his dedication towards the Goddess Durga, whom he addresses with different names like ‘Mai’, ‘Ma’ and ‘Mother’. He worships her power and expresses deep reverence for annihilating the evil-spirits. The festival Durga Puja also reminds people of victory of the goddess on the elusive demons in the battlefield. “Chasing a Dream on the Ganges” is another poem having spiritual overtones. Similarly, the poem “Akshya Tritya” has religious and spiritual connotations. It reflects curiosity of people for celebration of “Akshya Tritya” with enthusiasm. But the political and economic overtones cannot be ignored as the poem ends with the remarkable comments:The GDP may go up on this day;Even, Budia is able toEat to his fill; Panditji can blow hisConch shell with full might.Outside, somebody is asking for votes;Somebody is urging others to vote.I shall vote for Akshya Tritya. (65-66)         “On Reading Langston Hughes’ ‘Theme for English B’” is a long poem in the collection. In this poem, the poet reveals a learner’s craving for learning, perhaps who comes from an extremely poor background to pursue his dreams of higher education. The poet considers the learner’s plights of early childhood, school education and evolutionary spirit. He associates it with Dronacharya and Eklavya to describe the mythical system of education. He does not want to be burdened with the self-guilt by denying the student to be his ‘guru’ therefore, he accepts the challenge to change his life. Finally, he shows his sympathy towards the learner and decides to be the ‘guru’: “It is better to face/A challenge and change/Than to be burden with a life/Of self-guilt. /I put my signatures on his form willy-nilly” (11).         The poem “The Destitute” is an ironical presentation of the modern ways of living seeking pleasure in the exotic locations all over the world. It portrays the life of a person who has to leave his motherland for earning his livelihood, and has to face an irreparable loss affecting moral virtues, lifestyle, health and sometimes resulting in deaths. The poem “The Black Experience” deals with the suppression of the Africans by the white people. The poem “Me, A Black Doxy”, perhaps points out the dilemma of a black woman whether she should prostitute herself or not, to earn her livelihood. Perhaps, her deep consciousness about her self-esteem does not allow her to indulge in it but she thinks that she is not alone in objectifying herself for money in the street. Her voice resonates repeatedly with the guilt of her indulgence on the filthy streets:At the dining timeMe not alone? In the crowded streetMe not alone?They ’ave white, grey, pink hairMe ’ave black hair – me not aloneThere’s a crowd with black hair.Me ’ave no black moneyMe not alone? (14)         The poem “Thus Spake a Woman” is structured in five sections having expressions of the different aspects of a woman’s love designs. It depicts a woman’s dreams and her attraction towards her lover. The auditory images like “strings of a violin”, “music of the violin” and “clinch in my fist” multiply intensity of her feelings. With development of the poem, her dreams seem to be shattered and sadness know the doors of her dreamland. Finally, she is confronted with sadness and is taken back to the past memories reminding her of the difficult situations she had faced.         Replete with poetic irony, “Bubli Poems” presents the journey of a female, who, from the formative years of her life to womanhood, experienced gender stereotypes, biased sociocultural practices, and ephemeral happiness on the faces of other girls around her. The poem showcases the transformation of a village girl into a New Woman, who dreams her existence in all types of luxurious belongings rather than identifying her independent existence and finding out her own ways of living. Her dreams lead her to social mobility through education, friendships, and the freedom that she gains from her parents, family, society and culture. She attempts her luck in the different walks of human life, particularly singing and dancing and imagines her social status and wide popularity similar to those of the famous Indian actresses viz. Katrina and Madhuri Dixit: “One day Bubli was standing before the mirror/Putting on a jeans and jacket and shaking her hips/She was trying to be a local Katrina” (41). She readily bears the freakish behaviour of the rustic/uncultured lads, derogatory comments, and physical assaults in order to fulfil her expectations and achieves her individual freedom. Having enjoyed all the worldly happiness and fashionable life, ultimately, she is confronted with the evils designs around her which make her worried, as if she is ignorant of the world replete with the evils and agonies: “Bubli was ignorant of her agony and the lost calm” (42). The examples of direct poetic irony and ironic expressions of the socio-cultural evils, and the different governing bodies globally, are explicit in this poem: “Bubli is a leader/What though if a cheerleader./The news makes her family happy.”(40), “Others were blaming the Vice-Chancellor/ Some others the system;/ Some the freedom given to girls;”(45), and “Some blame poverty; some the IMF;/ Some the UN; some the environment;/ Some the arms race; some the crony’s lust;/ Some the US’s craving for power;/Some the UK’s greed. (46-47). Finally, Bubli finds that her imaginative world is fragile. She gives up her corporeal dreams which have taken the peace of her mind away. She yearns for shelter in the temples and churches and surrenders herself before deities praying for her liberation: “Jai Kali,/ Jai Mahakali, Jai Ma, Jai Jagaddhatri,/ Save me, save the world.” (47).         In the poem “The Unlucky”, the poet jibes at those who are lethargic in reading. He identifies four kinds of readers and places himself in the fourth category by rating himself a ‘poor’ reader. The first three categories remind the readers of William Shakespeare’s statement “Some are born great, some achieve greatness, and some have greatness thrust upon them.” At the end of the poem, the poet questions himself for being a poet and teacher. The question itself reflects on his ironic presentation of himself as a poor reader because a poet’s wisdom is compared with that of the philosopher and everybody worships and bows before a teacher, a “guru”, in the Indian tradition. The poet is considered the embodiment of both. The poet’s unfulfilled wish to have been born in Prayagraj is indexed with compunction when the poem ends with the question “Why was I not born in Prayagraj?” (52). Ending with a question mark, the last line of the poem expresses his desire for perfection. The next poem, “Saying Goodbye”, is elegiac in tone and has an allusion to Thomas Gray’s “The Elegy Written in a Country Churchyard” in the line “When the curfew tolls the knell of the parting day”; it ends with a question mark. The poem seems to be a depiction of the essence and immortality of ‘time’. Reflecting on the poet’s consideration of the power and beauty of ‘time’, Pradeep Kumar Patra rightly points out, “It is such a phenomena that nobody can turn away from it. The moment is both beautiful as well as ferocious. It beautifies and showcases everything and at the same time pulls everything down when necessary” (146). Apparently, the poem “The Kerala Flood 2018”is an expression of emotions at the disaster caused by the flood in 2018. By reminding of Gandhi’s tenets to be followed by people for the sake of morality and humankind, the poet makes an implicit criticism of the pretentions, and violation of pledges made by people to care of other beings, particularly, cow that is worshiped as “mother” and is considered to be a symbol of fertility, peace and holiness in Hinduism as well as the Buddhist culture. The poet also denigrates people who deliberately ignore the sanctity of the human life in Hinduism and slaughter the animal cow to satisfy their appetites. In the poem, the carnivorous are criticized explicitly, but those who pretend to be herbivorous are decried as shams:If a cow is sacrosanctAnd people eat beefOne has to take a side.Some of the friends chose toSide with cow and othersWith the beef-eaters.Some were more humanThey chose both. (55)The poet infuses positivity into the minds of the Indian people. Perhaps, he thinks that, for Indians, poverty, ignorance, dirt and mud are not taboos as if they are habitual to forbear evils by their instincts. They readily accept them and live their lives happily with pride considering their deity as the preserver of their lives. The poem “A Family by the Road” is an example of such beliefs, in which the poet lavishes most of his poetic depiction on the significance of the Lord Shiva, the preserver of people in Hinduism:Let me enjoy my freedom.I am proud of my poverty.I am proud of my ignorance.I am proud of my dirt.I have a home because of these.I am proud of my home.My future is writ on the wallsOf your housesMy family shall stay in the mud.After all, somebody is neededTo clean the dirt as well.I am Shiva,Shivoham. (73)         In the poem “Kabir’s Chadar”, the poet invokes several virtues to back up his faith in spirituality and simplicity. He draws a line of merit and virtue between Kabir’s Chadar which is ‘white’ and his own which is “thickly woven” and “Patterned with various beautiful designs/ In dark but shining colours” (50). The poet expresses his views on Kabir’s ‘white’ Chadar symbolically to inculcate the sense of purity, fortitude, spirituality, and righteousness among people. The purpose of his direct comparison between them is to refute artificiality, guilt and evil intents of humanity, and propagate spiritual purity, the stark simplicities of our old way of life, and follow the patience of a saint like Kabir.         The poem “Distancing” is a statement of poetic irony on the city having two different names known as Bombay and Mumbai. The poet sneers at its existence in Atlas. Although the poet portraits the historical events jeering at the distancing between the two cities as if they are really different, yet the poet’s prophetic anticipation about the spread of the COVID-19 in India cannot be denied prima facie. The poet’s overwhelming opinions on the overcrowded city of Bombay warn humankind to rescue their lives. Even though the poem seems to have individual expressions of the poet, leaves a message of distancing to be understood by the people for their safety against the uneven things. The poem “Crowded Locals” seems to be a sequel to the poem “Distancing”. Although the poet’s purpose, and appeal to the commonplace for distancing cannot be affirmed by the readers yet his remarks on the overcrowded cities like in Mumbai (“Crowded Locals”), foresee some risk to the humankind. In the poem “Crowded Locals”, he details the mobility of people from one place to another, having dreams in their eyes and puzzles in their minds for their livelihood while feeling insecure especially, pickpockets, thieves and strangers. The poet also makes sneering comments on the body odour of people travelling in first class. However, these two poems have become a novel contribution for social distancing to fight against the COVID-19.In the poem “Buy Books, Not Diamonds” the poet makes an ironical interpretation of social anarchy, political upheaval, and threat of violence. In this poem, the poet vies attention of the readers towards the socio-cultural anarchy, especially, anarchy falls on the academic institutions in the western countries where capitalism, aristocracy, dictatorship have armed children not with books which inculcate human values but with rifles which create fear and cause violence resulting in deaths. The poet’s perplexed opinions find manifestation in such a way as if books have been replaced with diamonds and guns, therefore, human values are on the verge of collapse: “Nine radiant diamonds are no match/ To the redness of the queen of spades. . . . / … holding/ Rifles is a better option than/ Hawking groundnuts on the streets?” (67).The poet also decries the spread of austere religious practices and jihadist movement like Boko Haram, powerful personalities, regulatory bodies and religious persons: “Boko Haram has come/Obama has also come/The UN has come/Even John has come with/Various kinds of ointments” (67).         The poem “Lost Childhood” seems to be a memoir in which the poet compares the early life of an orphan with the child who enjoys early years of their lives under the safety of their parents. Similarly, the theme of the poem “Hands” deals with the poet’s past experiences of the lifestyle and its comparison to the present generation. The poet’s deep reverence for his parents reveals his clear understanding of the ways of living and human values. He seems to be very grateful to his father as if he wants to make his life peaceful by reading the lines of his palms: “I need to read the lines in his palm” (70).         In the poem “A Gush of Wind”, the poet deliberates on the role of Nature in our lives. The poem is divided into three sections, perhaps developing in three different forms of the wind viz. air, storm, and breeze respectively. It is structured around the significance of the Nature. In the first section, the poet lays emphasis on the air we breathe and keep ourselves fresh as if it is a panacea. The poet criticizes artificial and material things like AC. In the second section, he depicts the stormy nature of the wind scattering papers, making the bed sheets dusty affecting or breaking the different types of fragile and luxurious objects like Italian carpets and lamp shades with its strong blow entering the oriels and window panes of the houses. Apparently, the poem may be an individual expression, but it seems to be a caricature on the majesty of the rich people who ignore the use of eco-chic objects and disobey the Nature’s behest. In the third and the last section of the poem, the poet’s tone is critical towards Whitman, Pushkin and Ginsberg for their pseudoscientific philosophy of adherence to the Nature. Finally, he opens himself to enjoy the wind fearlessly.         The poems like “A Voice” , “The New Year Dawn”, “The New Age”, “The World in Words in 2015”, “A Pond Nearby”, “Wearing the Scarlet Letter ‘A’”, “A Mock Drill”, “Strutting Around”, “Sahibs, Snobs, Sinners”, “Endless Wait”, “The Soul with a New Hat”, “Renewed Hope”, “Like Father, Unlike Son”, “Hands”, “Rechristening the City”, “Coffee”, “The Unborn Poem”, “The Fountain Square”, “Ram Setu”, and “Connaught Place” touch upon the different themes. These poems reveal poet’s creativity and unique features of his poetic arts and crafts.         The last poem of the collection “Stories from the Mahabharata” is written in twenty-five stanzas consisting of three lines each. Each stanza either describes a scene or narrates a story from the Mahabharata, the source of the poem. Every stanza has an independent action verb to describe the actions of different characters drawn from the Mahabharata. Thus, each stanza is a complete miniscule poem in itself which seems to be a remarkable characteristic of the poem. It is an exquisite example of ‘Micro-poetry’ on paper, remarkable for its brevity, dexterity and intensity. The poet’s conscious and brilliant reframing of the stories in his poem sets an example of a new type of ‘Found Poetry’ for his readers.         Although the poet’s use of various types images—natural, comic, tragic, childhood, horticultural, retains the attention of readers yet the abundant evidences of anaphora reflect redundancy and affect the readers’ concentration and diminishes their mental perception, for examples, pronouns ‘her’ and ‘we’ in a very small poem “Lost Childhood”, articles ‘the’ and ‘all’ in “Crowded Locals”, the phrase ‘I am proud of’  in “A Family by the Road” occur many times. Svitlana Buchatska’s concise but evaluative views in her Afterword to Unwinding Self  help the readers to catch hold of the poet’s depiction of his emotions. She writes, “Being a keen observer of life he vividly depicts people’s life, traditions and emotions involving us into their rich spiritual world. His poems are the reflection on the Master’s world of values, love to his family, friends, students and what is more, to his beloved India. Thus, the author reveals all his beliefs, attitudes, myths and allusions which are the patterns used by the Indian poets” (150).         W. H. Auden defines poetry as “the clear expression of mixed feelings.” It seems so true of Susheel Sharma’s Unwinding Self. It is a mixture of poems that touch upon the different aspects of human life. It can be averred that the collection consists of the poet’s seamless efforts to delve into the various domains of the human life and spot for the different places as well. It is a poetic revue in verse in which the poet instils energy, confidence, power and enthusiasm into minds of Indian people and touches upon all aspects of their lives. The poverty, ignorance, dirt, mud, daily struggle against liars, thieves, pickpockets, touts, politician and darkness have been depicted not as weaknesses of people in Indian culture but their strengths, because they have courage to overcome darkness and see the advent of a new era. The poems teach people morality, guide them to relive their pains and lead them to their salvation. Patricia Prime’s opinion is remarkable: “Sharma writes about his family, men and women, childhood, identity, roots and rootlessness, memory and loss, dreams and interactions with nature and place. His poised, articulate poems are remarkable for their wit, conversational tone and insight” (138). Through the poems in the collection, the poet dovetails the niceties of the Indian culture, and communicates its beauty and uniqueness meticulously. The language of the poem is lucid, elevated and eloquent. The poet’s use of diction seems to be very simple and colloquial like that of an inspiring teacher.On the whole the book is more than just a collection of poems as it teaches the readers a lot about the world around them through a detailed Glossary appended soon after the poems in the collection. It provides supplementary information about the terms used abundantly in Indian scriptures, myths, and other religious and academic writings. The Glossary, therefore, plays pivotal role in unfolding the layers of meaning and reaching the hearts of the global readers. The “Afterwords” appended at the end, enhances readability of poems and displays worldwide acceptability, intelligibility, and popularity of the poet. The Afterwords are a good example of authentic Formalistic criticism and New Criticism. They indirectly teach a formative reader and critic the importance of forming one’s opinion, direct reading and writing without any crutches of the critics.